Pengaruh Konflik Peran dan Ambiguitas Peran Terhadap Kinerja Karyawan dengan Stres Kerja Sebagai Variabel Intervening Pada PT. Bank SulutGo - Rifai, Rizka Putri (Universitas Sam Ratulangi, 2019)
This the research objective was to find out the effect of role conflict and role ambiguity directly on work stress at PT. Bank SulutGo, and to find out the effect of role conflict, role ambiguity, and work stress directly and indirectly towards the employee's performance at PT. Bank SulutGo. The results of hypothesis testing indicated that (I) the role conflict has a positive and signiï¬cant effect on work stress, role ambiguity has a negative and significant effect on work stress. (II) Role conflict not significan indirect affect the employee performance through work stress directly and role ambiguity significantly affects the employee performance through work stress of PT. Bank SulutGo directlyKeywords: Role conflict, role ambiguity, employees performance, work stress